(untitled) (Issues in Social and Environmental Accounting (ISEA), 2025)
Transfer pricing serves as a fundamental mechanism for multinational enterprises in managing cross-border operations, yet it presents significant ethical challenges when used for aggressive tax avoidance. This concept paper discusses the two sides of transfer pricing as a strategic business instrument and a possible aggressive tax avoidance tool. It explores the regulatory issues and the ethical considerations of transfer pricing practices with particular emphasis on the position of the tax authorities, multinational corporations, intermediaries and the changing regulatory environment. The paper highlights the increased significance of transparency, corporate social responsibility (CSR) and ethical governance in dealing with the risks related to transfer pricing. The paper ends with the recommendations on how to improve global coordination, better governance of taxes, and encourage responsible taxation by multinational enterprises. The paper proposes a new approach to transfer pricing that aligns with CSR principles, suggesting three key reforms: incorporating tax disclosures into sustainability reports, implementing OECD guidelines as ethical standards, and establishing collaborative forums for tax policy development. By redefining responsible tax behavior as a core component of corporate citizenship, this research provides practical guidance for business leaders and contributes to ongoing discussions about ethical governance in global business